ANALYSIS OF TYPES AND ECONOMIC VALUE OF NON-TIMBER FOREST PRODUCTS OF THE CONSERVATION PARTNERSHIP FOREST FARMER GROUP OF WAN ABDUL RACHMAN FOREST PARK - Setiawan, Birgita Diah Puspitrani; Kaskoyo, Hari; Wulandari, Christine; Bakri, Samsul; Fitriana , Yulia Rahma; Febryano, Indra Gumay (Jurnal Belantara, 2025)
Non-timber forest product resources are valuable to communities around the forest which are more useful than wood in the long term and can provide good benefits from the ecosystem for sustainability, conservation, and the economy. The research aims to identify the types and economic value of non-timber forest products commodities from Conservation Partnership Forest Farmer Groups in Wan Abdul Rachman Forest Park. Data collection was carried out using interviews, literature studies and documentation. The data that has been collected is then analyzed using a Likert Scale. The method used is to calculate the economic value of each type of non-timber forest product and group it based on the highest commodity. According to the research findings, the primary commodities of Mekar Sari Forest Farmer Group are nutmeg, coffee, and cacao, while Wana Karya Forest Farmer Group's are rubber, petai, and king fruit, and Maju Lestari Forest Farmer Group's are king fruit, nutmeg, and coffee. Coffee has an economic impact of 25.01% at Mekar Sari Forest Farmer Group, 30.58% at Wana Karya Forest Farmer Group, and 36.03% at Maju Lestari Forest Farmer Group. The economic values of Forest Farmer Groups are IDR 209,375,000/year, IDR 971,444,000/year, and IDR 313,384,200. According to the calculation method, the average revenue earned from non-timber forest products is IDR 6,979,166/household/year, IDR 28,571,882/household/year, and IDR 10,594,906/household/year.